Structure of a general solution of systems of nonlinear difference equations - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate the structure of a general solution of systems of nonlinear difference equations with continuous argument in a neighborhood of the state of equilibrium.